Sustainable of flora resources in socioeconomic of hunters and gatherers community in Malaysia - Mohamad Hafis, A.S.; Ramle, Abdullah; Mohamad Asmawi, Ibrahim (2016)
Aboriginal tribes of Semaq Beri is one of the community of Malaysia aborigines, that still applied the life style like hunting and gathering wildlife resources. Most of the tribes like Semaq Beri use forest as their place to work of various activities in life. Their life we depend on a close relationship with jungle has formed this Semaq Beri tribes with vast knowledge and skills which very significant, especially when it comes towards the relation to the resources that can be useful and manipulated for the benefit of the flora life. However, there are worries regarding the preservation of the flora which it is the only source that they depend on, for their daily lives. Due to the decreasing forest space and the present of other communities get the flora resource s, on which it came from the same spot of forest have threatened their resources.